AN UPDATE ON DIAGNOSIS AND MANAGEMENT OF THROMBOEMBOLISM IN PREGNANCY - ULLAH, S; FAWAD, K; SHAHBAZ, N; KHAN , N; KHAN, KS; KHAN, H (Biological and Clinical Sciences Research Journal, 2024)
Thromboembolism during pregnancy poses a significant challenge in maternal healthcare, substantially contributing to maternal morbidity and mortality worldwide. Understanding its diagnosis and management is crucial for improving maternal and fetal outcomes. Objective: To evaluate the diagnosis and management of thromboembolism in pregnant women. Methods: A retrospective cohort study was conducted at Lady Reading Hospital, Peshawar, from July 2022 to July 2024. The study included 175 pregnant females diagnosed with venous thromboembolism (VTE) during their pregnancy. Data were collected on patient demographics, trimester of diagnosis, type of thromboembolism (deep vein thrombosis [DVT] or pulmonary embolism [PE]), treatment modalities, and outcomes. Patients were treated with either low molecular weight heparin (LMWH) or unfractionated heparin (UFH). Descriptive statistics were used to analyze the data, with results presented as percentages and means with standard deviations. Results: The mean age of the participants was 32.01 ± 2.35 years. Thromboembolism was most commonly diagnosed in the third trimester (65%), followed by the second trimester (25%) and the first trimester (10%). DVT was observed in 74% of patients, while PE occurred in 26%. Among the 160 patients treated with LMWH, 3% (5 patients) experienced a recurrence of VTE. Of the 15 patients who received UFH, 5% (8 patients) had significant bleeding complications. Overall maternal outcomes included a 3% recurrence rate of VTE and a 5% rate of significant bleeding complications. No maternal mortality was reported. Conclusion: Early diagnosis and timely management of thromboembolism in pregnancy, mainly through the use of low molecular weight heparin and a multidisciplinary care approach, significantly improve maternal and fetal outcomes. LMWH was associated with fewer complications compared to UFH, highlighting its effectiveness and safety in treating pregnant women with VTE.